Atividade antitumoral da Morinda citrifolia sobre o Tumor de Ehrlich: ensaio in vitro e in vivo. - ROCHA, Alessandra Lima (2017)
Given the concern about the high incidence of neoplasias and the low specificity of available antineoplastic agents, some herbal medicines have been used as food supplements, immunomodulators and antitumorals. Morinda citrifolia is a medicinal plant known to have several biological activities, such as anti inflammatory, antiviral, antioxidant, anti-tumor, etc. The present study had as objective to evaluate the antitumor activity of the hydroalcoholic extract of the fruit of M. citrifolia in Swiss mice with Ehrlich ascitic tumor. The animals were divided into 8 groups: negative control, treated with hydroalcoholic extract of the M. citrifolia fruit at concentrations of 125, 250, 500mg / kg / day, cyclophosphamide 40mg / kg / day and combinations of cyclophosphamide with the hydroalcoholic extract of M Citrifolia at concentrations 125, 250, 500mg / kg / day. Clinical evaluations of tumor development, hematological, Th1, Th2 and Th17 cytokine dosages and evaluation of the apoptosis rate by annexin V were performed. In vitro splenocytes were cultured for 48 hours for Th1 type cytokine dosing, Th2 and Th17. The hydroalcoholic extract of the M. citrifolia fruit had no antitumor activity, leading to a more hemorrhagic appearance of the tumor. The combination of hydroalcoholic extract of the M. citrifolia fruit with cyclophosphamide had no higher performance in antitumor activity, when compared to conventional treatment, but the total number of leukocytes was higher in the groups with the associations. Treatment with the hydroalcoholic extract of the Morinda citrifolia fruit and association with cyclophosphamide did not alter cytokine levels in vitro or in vivo in animals inoculated with Ehrlich tumor. In conclusion, the hydroalcoholic extract of Morinda citrifolia showed no antitumor activity, but led to a slight increase in leukocyte count when associated with cyclophosphamide.